Geochemical features of fluid in Xiaojiang fault zone, Southeastern Tibetan plateau: Implications for fault activity. (January 2023) - He, Hongyi; Chen, Zhi; Liu, Zhaofei; Gao, Zihan; Hu, Le; Lu, Chang; Shao, Junjie; Li, Ying
Abstract: It is well established that fluid geochemistry in fault zones could provide reliable indicators for fault activity. Along these lines, in this work, Rn and CO2 fluxes were measured for soil gases along the Xiaojiang Fault Zone (XFZ), SW China. The relationship among the soil gas Rn and CO2 fluxes, hydrochemistry of hot springs, and fault activity were thoroughly examined based on the analytical results and regional geology. The water samples from the hot springs in the study area were the primary types of Ca·Mg-HCO3, Ca·Mg-HCO3 ·SO4, and Ca-SO4 . It was believed that these types were probably affected by the interactions between the groundwater and carbonate rocks. Based on the weak correlation between the soil gas Rn and the CO2 fluxes, the existence of distinct sources was suggested. The manifestation of a relatively high temperature and ion concentration of the hot spring water samples, as well as the relatively high soil gas Rn and CO2 fluxes, led to a concentrated distribution in the northern and southern segments of the XFZ, which was consistent with the spatial distribution of the seismic activities and fault slip rate. The intense fault activity in the southern and northern segments could also enhance the permeability and accelerate both the water-rock interactions and soil gas emission within the fault zone. An assessment of the earthquake potential and radioactivity protection is considered of outmost significance for the southern and northern segments of the XFZ. Highlights: Feature and genesis of fluids emitted from the XFZ were systematically analyzed. Hydrochemistry and soil gas Rn are potential indicators to evaluate fault activity. Attention should be paid to seismicity and radiation risk in two ends of the XFZ.